(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Sukmasuang R, Charaspet K, Reontik J, Pla-ard M. 2020. Temporal overlap of carnivorous mammal community and their prey in Khao Ang Rue Nai Wildlife sanctuary, Chachoengsao Province, Thailand. Biodiversitas 21: 922-932. This study on the temporal overlap of the carnivorous community and their prey in Khao Ang Rue Nai Wildlife Sanctuary was conducted from March 2017 to February 2018. Camera traps were deployed systematically with a total of 4,463 trap nights. Fourteen carnivorous mammals were recorded, which were mainly present at night, with the exception of the dhole, small Indian mongoose, crab-eating mongoose, and yellow-throated marten. The clouded leopard’s presence overlapped between day and night. Using the average coefficient overlap(?) between a carnivore, and the other carnivorous species, the leopard cat was found to have the highest ? value, followed by the hog badger, Asiatic jackal, small Indian civet, Asian palm civet, large Indian civet, large spotted civet, Asiatic black bear, dhole, Malayan sun bear, yellow-throated marten, small Indian mongoose, crab-eating mongoose, and clouded leopard. The potential prey species that had the highest ?with the carnivorous species, was the Siamese hare. This study shows the importance of preserving the carnivorous community within the area. An important threat is a likelihood that carnivorous species in the area may be exposed to external diseases from infected domestic animals when coming out to hunt in the communities surrounding the protected area.